Cosmopolitical Ecologies Across Asia Places and Practices of Power in Changing Environments (Taylor & Francis, 2022)
Cosmopolitical Ecologies Across Asia offers a unique insight into the non-human and spiritual dimensions of environmental management in a changing world. This volume presents a comparative, place-based exploration of landscapes across Asia and the entities, practices and knowledges that inhabit them. Rather than treating sacred mountains, terrains and water sources as self-contained, esoteric religious phenomena, the authors consider them within critical 'cosmopolitical ecologies' framings in which non-human entities are engaged as actors in the socio-political arena. The chapters include case studies of healing springs recognized by governments, and sacred mountains that are addressed by heads of states and Communist Party cadres, or that speak to the faithful through spirit mediums in a politics of re-enchantment. Contributors explore the diverse ways in which non-human entities such as forest spirits, reindeer, mountains and Buddhist Masters of the Land are engaged by humans to navigate environmental change and address a range of ecological threats from large-scale mining to climate change. Cosmopolitical ecologies approaches encompass the healing power of topography as well as transformative intimacies with other-than-human beings such as sparrows within an Islamic eco-theological poetic setting. In this light the book observes dynamic and creative processes of cosmological innovation including the repurposing of ritual to address challenges such as the Covid-19 epidemic. This book will be of great interest to students and scholars of environment and society across disciplinary perspectives in general, and to anthropologists, human geographers, political ecologists, indigenous studies, area studies, environmental sciences and environmental humanities scholars in particular.
English
Keywords: Cosmopolitical Ecologies,landscapes,mountains,terrains,water sources,socio-political,Holy Mountain,Young Man,Uninvited Guests,Cosmopolitical Ecologies,Central Tibetan Administration,Mae Chaem,Yul Lha,China Town,Limi Valley,Reindeer Herders,Je Khenpo,Sacred Natural Sites,Mountain Deities,Natural Beauty,Landscape Deities,Haze Crisis,Bull Camel,Bhutanese Context,Territorial Deities,Nonhuman Personhood,Contract Farming,Non-human Persons,Tibetan Landscapes,Political Ecology,Dpal Ldan; thema EDItEUR::J Society and Social Sciences::JH Sociology and anthropology::JHM Anthropology; thema EDItEUR::Q Philosophy and Religion::QR Religion and beliefs; thema EDItEUR::R Earth Sciences, Geography, Environment, Planning::RN The environment::RNC Applied ecology